Evaluasi Perkuliahan Genetika untuk Calon Guru Biologi di Universitas Nusantara PGRI Kediri - Poppy Rahmatika Primandiri; Agus Muji Santoso (Universitas Sebelas Maret, 2015)
Biology teachers are expected to have competence of 21st century skills, including mastering aspects of genetic material that continues to be advented. Therefore, studies that aim to empower genetic study needs to be done. This study aimed to describe some of the obstacles encountered during the course of genetics for prospective teachers UNP Biology in Kediri to be immediately followed up. This research was a case study, conducted by participant observation for three academic years (2013 - 2015) in the lecture class genetics. This study shown that the unavailability of relevant teaching materials, genetics practices were not supported of the concept, yet supported tools - genomic analysis, and lecturing genetics have not utilized the development of genomic data base that continues to grow. This condition causes the students still have misconceptions about the structure of the genetic structure, the regulation of gene expression, mutation, and recombination of genes.Keywords: genetics, biology teachers, program evaluation